Kritik Representasi Masyarakat Marginal dalam Lagu Falasteen Biladi Karya Humood Al-Khudher Perspektif Poskolonial - Azis, Rifa Salma; Bakar, Irfan Abu; Rokhim, Minatur; Fazillah, Nadya Nasywah; Maulida, Silmi (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study examines the critique of the representation of marginalized communities in the lyrics of Humood al-Khudher's song "Falasteen biladi" through Gayatri Spivak's postcolonial theoretical framework, particularly the concepts of subalternity and representation. The purpose of this study is to critically analyze the representation of marginalized Palestinian communities. This study uses a qualitative approach with critical textual analysis methods. The research method is a literature review. The main data source is the lyrics of the song Falasteen biladi, both in Arabic and in translation. The secondary data source is Gayatri Spivak's theoretical book, specifically her essay entitled “Can the subaltern speak?” The data collection techniques are documentation, literature study, and contextual research. Data analysis uses three main analytical frameworks, namely Darstellung, Vertretung, and Epistemic Violence. The findings of this study show that the lyrics of this song. The findings show that the lyrics of this song depict Palestine more as an abstract collective subject, thereby ignoring the diversity of individual experiences and the complexity of the social and political realities they face. In addition, there is a dominance of narrative representation over political representation, which tends to reduce the Palestinian struggle to aesthetic symbolism rather than concrete political advocacy. Finally, this song reveals the limitations in expressing authentic subaltern voices, where what stands out is the cultural elite's perspective on marginalized communities. Despite attempting to foster solidarity, this song maintains epistemic silencing, where subalterns remain voiceless due to the dominance of a strong hegemonic narrative. The implications of this research emphasize the importance of critical reflection on the politics of representation in popular cultural productions about marginalized communities.